Study of the Components and Indicators of Effectiveness of Secondary Schools in Hormozgan Province in order to provide a model for improving the educational system in schools - javad imani; Mehdi Bagheri; parivash jafari; nader gholi ghourchian (Allameh Tabataba'i University Press, 2017)
The dissatisfaction from the educational system's performance to answer the increasing needs of the today society and the weak caoabilities of its outputs to achive the pre determind objectives, have confronted the todey's education with serious challenges. accordingly, the present study was aimed to Study of the Components and Indicators of Effectiveness of Secondary Schools in Hormozgan Province in order to provide a model for improving the educational system in schools. the purpose of this research is applied and in terms of information gathering method, a quantitative-qualitative approach has been taken. the statistical population includes experts in the field of school effectiveness which in part of quantitative research, included all school principals, teachers and students in Hormozgan province during the academic year of 2017-18 (N=6800), also In the qualitative section, the statistical population was estimated with a theoretical saturation of 10 people. the sample size was estimated to be 364 by Cochran formula. A stratified sampling was used to select the sample. The data collection tool was a researcher-made questionnaire based on the 5-item scale. Reliability of the questionnaire through Cronbach's alpha and Validity of the questionnaire in terms of form and content were confirmed through several experts. To analyze the data, exploratory factor analysis and confirmatory factor analysis were used. The results obtained to identify 16 components and 65 indicators, whose naming was based on theoretical foundations.